2009
DOI: 10.1007/s11207-009-9470-2
|View full text |Cite
|
Sign up to set email alerts
|

How Can a Negative Magnetic Helicity Active Region Generate a Positive Helicity Magnetic Cloud?

Abstract: The geoeffective magnetic cloud (MC) of 20 November 2003 was associated with the 18 November 2003 solar active events in previous studies. In some of these, it was estimated that the magnetic helicity carried by the MC had a positive sign, as did its solar source, active region (AR) NOAA 10501. In this article we show that the large-scale magnetic field of AR 10501 has a negative helicity sign. Since coronal mass ejections (CMEs) are one of the means by which the Sun ejects magnetic helicity excess into interp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
83
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(99 citation statements)
references
References 87 publications
10
83
1
Order By: Relevance
“…Vemareddy et al (2012b) recognized that major flaring activity only occurred at times when helicity was injected in the AR with a sign opposite to the dominant sign of the AR (see also Kusano et al 2002). Similar findings have been presented for CME- (Wang et al 2004) and MC-productive (Chandra et al 2010) ARs. For these too, the sign of the helicity inherent to the newly emerging magnetic flux systems may well be opposite to that of the dominant helicity in the pre-existing active-region magnetic field.…”
Section: Helicity Buildup and Storagesupporting
confidence: 55%
See 1 more Smart Citation
“…Vemareddy et al (2012b) recognized that major flaring activity only occurred at times when helicity was injected in the AR with a sign opposite to the dominant sign of the AR (see also Kusano et al 2002). Similar findings have been presented for CME- (Wang et al 2004) and MC-productive (Chandra et al 2010) ARs. For these too, the sign of the helicity inherent to the newly emerging magnetic flux systems may well be opposite to that of the dominant helicity in the pre-existing active-region magnetic field.…”
Section: Helicity Buildup and Storagesupporting
confidence: 55%
“…But events have also been reported where this has not been the case. For instance, Chandra et al (2010) investigated a case in which observed features (sunspot whorls and flare ribbons) as well as a corresponding LFF magnetic field suggested a predominantly negative helicity within an AR. In contrast, the associated MC was attested a positive helicity, which contradicted helicity conservation.…”
Section: Helicity Dissipation and Transportmentioning
confidence: 99%
“…We interpret this correlation as an indication of the important role played by the coexistence of systems that are characterized by opposite signs of magnetic helicity in triggering eruptive events, as already pointed out in previous observations of single events (Chandra et al 2010;Romano et al 2011) and as shown in the numerical simulations of Linton et al (2001), Mok et al (2001) and Kusano et al (2004). Indeed, the interaction of magnetic fluxes with opposite helicity allows the release of the free energy because the field can relax to a state closer to a potential field through reconnection processes.…”
Section: Discussionsupporting
confidence: 83%
“…In particular, the deeper investigation of the helicity budget and the evolution of a single event as well as the knowledge of the topology of the AR where the event occurred allows one to better understand the particular conditions that bring magnetic field systems to interact and to release energy during eruptive events. Recently, several studies have shown that some eruptions occurred in regions that are characterized by the coexistence of two magnetic field systems with opposite signs of magnetic helicity (Yokoyama et al 2003;Chandra et al 2010;Romano et al 2011). Indeed, the magnetic helicity is a quantity with either a positive or a negative sign, which represents the right-handed linkage or the left-handed linkage of magnetic fluxes, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The first CME was detected in the C2 field-of-view at 08:06 UT and the second one was observed at 08:50 UT. Two days later, these CMEs produced the most powerful geomagnetic storm in solar cycle # 23 (Ermolaev et al 2005;Srivastava et al 2009;Chandra et al 2010). Figure 2 presents the line-of-sight magnetogram obtained by the Michelson Doppler Imager (MDI) on-board SOHO at 00:00 UT.…”
Section: Observations Of Noaa Ar 10501 On 2003 November 18mentioning
confidence: 99%